Interpretive Study On The Development Of Petanque Sports Athletes In Central Java - Witri Suwanto; Rizki Hazazi Ali; Rahmat Putra Perdana; Putra Sastaman Bustamin; Rubiyatno Rubiyatno; Dody Tri Iwandana (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2022)
The purpose of this study was to determine the Interpretive Study of the Development of Petanque Sports Athletes in Central Java. This research uses interpretive qualitative research. The sampling technique used in this research is purposive sampling or sampling purpose. There are three main data collection techniques in descriptive research, namely observation, interviews, and document analysis. The analysis in this study was carried out in four stages, namely; The stages of data collection, data reduction, data presentation, and conclusion drawing. From the results of the study, it can be concluded that the development of Petanque sports achievements is managed by each branch of the Central Java Indonesian Petanque Sports Federation (FOPI). So far there has been no special coaching related to talent search for early childhood development other than activities carried out on the UTP campus, UNNES, and extracurricular activities in schools such as elementary, junior high, and high school. The training camp in Semarang is still only carried out when approaching the multi-event by selecting outstanding athletes from each branch manager.